3D-additive deposition of an antibacterial and osteogenic silicon nitride coating on orthopaedic titanium substrate. (March 2020) - Zanocco, Matteo; Boschetto, Francesco; Zhu, Wenliang; Marin, Elia; McEntire, Bryan J.; Bal, B. Sonny; Adachi, Tetsuya; Yamamoto, Toshiro; Kanamura, Narisato; Ohgitani, Eriko; Yamamoto, Kengo; Mazda, Osam; et al.
Abstract: A 3D-additive manufacturing approach produced a dense Si3 N4 ceramic coating on a biomedical grade commercially pure titanium (cp-Ti) substrate by an automatic laser-sintering procedure. Si3 N4 coatings could be prepared with thicknesses from the single to the tens of microns. A coating thickness, t = 15 ± 5 μm, was selected for this study, based on projections of homogeneity and scratching resistance. The Si3 N4 coating met the 20 N threshold required for biomaterial applications, according to the standard scratch testing (ASTM C1624-05). The Si3 N4 coating imparted both the antibacterial and osteogenic properties of bulk Si3 N4 to the cp-Ti substrate. Both properties were comparable to those previously described for bulk Si3 N4 biomedical implants. The newly developed Si3 N4 -coating was applied to commercially available Ti-alloy acetabular shells for total hip arthroplasty. A "glowing" test based on luciferase gene transformation was applied to visualize the colonization of gram-negative Escherichia coli on Si3 N4 -coated and uncoated Ti-alloy acetabular shells. The results showed that the coating technology conferred resistance to Staphylococcus epidermidis and Escherichia coli adhesion onto the bulk acetabular sockets. Graphical abstract: Image 1